2020
DOI: 10.7759/cureus.7257
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Enterococcus faecalis as a Dental Root Canal Pathogen on Endodontic Treatment: A Systematic Review

Abstract: Endodontic treatment failure may occur due to different causes such as persistence of bacteria, root canals that are poorly cleaned and obturated, improper coronal seal (leakage), and untreated canals (missed canals). The main reason for endodontic failure is the presence of some species of bacteria inside the root canal system such as Enterococcus (E.) faecalis. Those bacteria are more resistant to disinfection agents, causing a persistent intra-radicular or extraradicular infection. The current review aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(170 citation statements)
references
References 24 publications
1
124
0
5
Order By: Relevance
“…In addition, E. faecalis is frequently identified in failed root canal treatment with persistent apical periodontitis (i.e. chronic inflammation and destruction of the hard and soft tissues surrounding the root/s of a tooth caused by etiological agents of endodontic infection) [24]. Persistent apical periodontitis occurs when root canal treatment of apical periodontitis has not adequately eliminated infection within the root canal space.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, E. faecalis is frequently identified in failed root canal treatment with persistent apical periodontitis (i.e. chronic inflammation and destruction of the hard and soft tissues surrounding the root/s of a tooth caused by etiological agents of endodontic infection) [24]. Persistent apical periodontitis occurs when root canal treatment of apical periodontitis has not adequately eliminated infection within the root canal space.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found that blackcurrant juice suppressed the gram-positive bacterial species E. faecalis completely ( Figure 2 ). E. faecalis , in particular, often withstands treatment with customary disinfectants and is therefore frequently responsible for root canal treatment failures [ 30 ]. Compared to the action of blackcurrant juice, CHX revealed a rather low antibacterial effect on E. faecalis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete elimination of debris and bacteria in the root canal system is impossible because of the complexity of the root canal anatomy [ 1 ]. The remnant bacteria, especially Enterococcus faecalis, are believed to be the most resistant microorganism that contribute to the persistent periradicular lesion after root canal treatment [ 2 ]. Different virulence factors, such as aggregation substance, lipoteichoic acid, and pheromones, have facilitated Enterococcus faecalis to survive in dentinal tubules up to 400 ÎĽm depth in a nutrient deficiency ecology environment and cause secondary infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%